Early Detection of Cancer: Immunoassays for Plasma Tumor Markers - Meany, Danni L. (2009)
BACKGROUND: Plasma tumor biomarkers are widely used clinically for monitoring response to therapy and detecting cancer recurrence. However, only a limited number of them have been effectively used for the early detection of cancer. OBJECTIVE: To review plasma tumor markers used clinically for the early detection of cancer and to provide expert opinion about future directions. METHODS: Literature review, as well as our expert opinion, of plasma tumor markers that have been widely accepted for the early detection of cancer. RESULTS: In the United States, only prostate specific antigen (PSA), cancer antigen 125 (CA125), and alpha-fetoprotein (AFP) have been clinically used for the early detection of prostate, ovarian, and liver cancers, respectively. Both analytical and clinical issues related to the use of these three markers were discussed. CONCLUSION: Few plasma tumor markers have been used effectively for the early detection of cancer, mainly due to their limited sensitivity and/or specificity. Multiple approaches have been developed to improve the clinical performance of tumor markers for the early detection of cancer. Metrological traceability and antibody specificity are important issues to ensure comparability of immunoassays for the measurement of plasma tumor markers.